Nonfamilial acrokeratosis verruciformis of Hopf - Nidhi Patel; Nilofar Diwan; Pragya A Nair (Wolters Kluwer Medknow Publications, 2015)
Acrokeratosis verruciformis (AKV) of Hopf is an autosomal dominant genodermatosis with unknown etiology. It is characterized by multiple flat-topped keratotic papules resembling planar warts located mainly on the dorsum of hands and feet. Superficial ablation is the treatment of choice. A 41-year-old female presented with multiple hyperpigmented, hyperkeratotic papules and plaques over flexor aspect of both forearms, extensors of both legs and dorsum of the feet. Histopathology showed changes of AKV. Patient was treated with a combination of topical corticosteroids and cryotherapy with no visible improvement.